Unhooking medicine [wireless networking]. - Moore, S.K.
In summer 2000, the FCC allocated 14 MHz for the Wireless Medical Telemetry Service, or WMTS. The new service is broken into three bands: 608-6I4, 1395-1400, and 1429-1432 MHz. The old bands will become increasingly troublesome to use in medicine. The ruling is forcing medical device firms to come up with fixes for their old devices and new technologies for the next generation of wireless telemetry. The new band allocation has pushed cash-strapped hospitals in the United States to the brink of an unwanted technology makeover. Hospitals are being forced to reengineer their patient-worn and bedside wireless systems, which could mean the purchase of new transmitters, receivers, and antennas. At the same time physicians and other health care workers are confronted with a whole raft of new wireless technologies, many involving accessing patient data through a personal digital assistant (PDA) or a wireless phone. While the WMTS offers a safe haven for telemetry signals, it has some technical limitations that may diminish its importance
Keywords: 1395 to 1400 MHz; 14 MHz; 1429 to 1432 MHz; 608 to 614 MHz; Wireless Medical Telemetry Service; Bedside wireless systems; Hospitals; Medical device firms; Patient data access; Patient-worn wireless systems; Personal digital assistant; Wireless networking; Wireless phone